VALIDITY AND RELIABILITY OF ESSAY DIAGNOSTIC TEST MATERIAL HEAT AND ITS TRANSFER VIITH GRADE - Mahsunah, Himmatul; Manasikana, Oktaffi Arinna (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2024)
The essay diagnostic test is a test that can be used as an instrument to identify learning difficulties based on student answers that are written by themselves. This study purposed to determine the validity and reliability of an essay diagnostic test on heat and its transfer, which is material in class VII SMP/MTs. Validity and reliability were obtained from validation tests and product trials. Validation tests were validated by two expert lecturers to determine theoretical validity, while product trials were used to determine empirical validity and reliability. The results of this study were 10 very valid questions theoretically with a score of 91.67%. Theoretical validity in material aspects of 92.5%, construct 83.75%, and language 98.75% are all very valid criteria. The validity of the question item theory shows that 9 questions are very valid, while 1 question is valid. Therefore, the expert validation test shows 10 theoretically valid questions, so it must be theoretically reliable as well. The empirical validity was only 9 questions with r11 = 0.891, so it had very high reliability. Therefore, nine questions from the essay diagnostic test on heat and its transfer, which is material in class VII SMP/MTs, are declared valid and reliable.